Identifikasi Akulturasi Budaya Pada Masjid Jami’ Kutablang Kecamatan Samalanga Kabupaten Bireuen (Studi kasus: Budaya Local Aceh, Cina, Timur Tengah dan Kolonial) - Zainab, S; Fithri, C. A; Andriani, D (Cered Indonesia Institute, 2025)
Aceh is a region with a strategic role as a center of international traffic networks. Its location on the edge of the Strait of Malacca makes it an important route for maritime trade and international interactions. Aceh has been a meeting place for various cultures and civilizations since the Neolithic era, enriching the culture and traditions of its people to this day. In this process, there has been a fusion and integration of diverse cultural elements, both local and foreign, which has created a unique characteristic in the architecture of buildings in Aceh. Acculturation is the process of interaction between two or more cultures that results in a new culture without erasing the distinctive features of each culture. One form of this is found in the building of the Masjid Jami' Kutablang Samalanga in Bireuen Regency, Aceh Province, which displays the fusion of local (Aceh), Chinese, Middle Eastern, and Colonial cultures. This study aims to identify the extent to which cultural influences have affected the architecture of the Masjid Jami' Samalanga and to examine the factors that led to the cultural acculturation in this mosque. This research is expected to provide new insights into the phenomenon of cultural acculturation in mosque architecture and its significant contribution to the preservation of cultural heritage in Aceh. The method used is descriptive qualitative with observations, interviews, and literature studies. The results of the study show that Masjid Jami' Kutablang Samalanga is the oldest mosque in Samalanga, built during the Dutch colonial period in 1901 by Teungku Haji Syekh Abdul Jalil upon his return from Saudi Arabia, with the involvement of a Chinese convert as the head carpenter. The acculturation of local Acehnese culture is evident in the roof, ornamentation, and orientation. Chinese culture is reflected in the roof, floor, and ornaments. Middle Eastern culture is visible in elements such as the dome, mihrab, minbar, minaret, and arches. Colonial culture is seen in the use of gevels, bouvenlicht, nok acroterie, geveltoppen, thick walls, dominant white color, symmetrical layout and facade, and cripedoma.